2021
DOI: 10.2478/raon-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation of immature oocytes for fertility preservation in cancer patients compared to control patients with fertility problems in an in vitro fertilization program

Abstract: Background The aim of this study was to determine whether in vitro maturation (IVM) of immature oocytes after controlled hormonal stimulation of the ovaries could be important in cancer patients to improve their chances of conception in the future. Patients and methods After ovarian stimulation in cancer patients, the number of oocytes and their quality and maturity were compared to control patients with fertility problems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…102 103 104 It has been shown that measuring serum AMH level can be used as a predictive marker for the success of IVM, influencing outcomes such as the number of mature oocytes obtained and the overall efficiency of the maturation process. 103 105 However, in women with cancer, oocyte maturation rates are lower than that in healthy women, 106 so this technique seems to be of more interest when pretreatment AMH level is high (>3.7 ng/mL) in order to obtain a minimum of 10 mature oocytes after IVM. 105 Thus, serum AMH level could be used to select women to be offered IVM technique.…”
Section: Amh and Art Outcome For Fertility Preservation: How Useful I...mentioning
confidence: 99%
“…102 103 104 It has been shown that measuring serum AMH level can be used as a predictive marker for the success of IVM, influencing outcomes such as the number of mature oocytes obtained and the overall efficiency of the maturation process. 103 105 However, in women with cancer, oocyte maturation rates are lower than that in healthy women, 106 so this technique seems to be of more interest when pretreatment AMH level is high (>3.7 ng/mL) in order to obtain a minimum of 10 mature oocytes after IVM. 105 Thus, serum AMH level could be used to select women to be offered IVM technique.…”
Section: Amh and Art Outcome For Fertility Preservation: How Useful I...mentioning
confidence: 99%
“…Therefore, although most centers adopt this protocol, labeled as IVF/M cycles, the outcome remains low to be translated into clinical pregnancy, although utilized among normal ovarian reserve women ( 31 ). Nevertheless, it can be reserved as an alternative fertility preservation (FP) strategy, primarily for women with a limited stimulation window, such as patients with cancer aiming for more mature oocytes for future use ( 32 ). Thus, utilizing IVM protocol in cycles that potentially harvest both immature and mature oocytes in the same cycle and using the hcg trigger are currently not considered standard IVM because not all oocytes were mature in vitro per se ( 10 , 22 ).…”
Section: Controversial Definition Of In Vitro Matu...mentioning
confidence: 99%
“…Furthermore, this study compared the number of mature oocytes obtained through IVM in groups of patients with different types of cancer and fertility problems. The results indicated that patients with breast cancer had a lower proportion of oocytes that matured in vitro compared to patients with other cancers and those with fertility problems (54.5% vs. 81.2% and 80.0%) [103,104]. In 2020, Malacarne et al [105] arrived at the conclusion that there was no significant difference in the mean number of oocytes retrieved for each breast cancer patient following ovarian stimulation, as compared to healthy control women, including oocyte donors, women undergoing fertility preservation for nonmedical reasons, and female partners of infertile men participating in an in vitro fertilization (IVF) program.…”
Section: In Vitro Maturation (Ivm)mentioning
confidence: 99%